2020
DOI: 10.1038/s41467-020-20022-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of regio- and stereo-specificity in biosynthesis of bacterial heterodimeric diketopiperazines

Abstract: Bacterial heterodimeric tryptophan-containing diketopiperazines (HTDKPs) are a growing family of bioactive natural products. They are challenging to prepare by chemical routes due to the polycyclic and densely functionalized backbone. Through functional characterization and investigation, we herein identify a family of three related HTDKP-forming cytochrome P450s (NasbB, NasS1868 and NasF5053) and reveal four critical residues (Qln65, Ala86, Ser284 and Val288) that control their regio- and stereo-selectivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(96 citation statements)
references
References 29 publications
3
84
0
Order By: Relevance
“…In another study, cyclo(L-Phe-L-Pro) produced by Vibrio vulnificus was found to activate the quorum sensing on an E. coli biosensor strain by modulating the expression of the gene encoding OmpU protein [231]. Finally, cyclo(L-Phe-L-Pro) and cyclo(L-Pro-L-Tyr) produced by Lactobacillus reuteri, were reported to interfere with quorum sensing in the Gram-positive S. Aureus [41,221,227,[232][233][234].…”
Section: Quorum-sensing Agonists and Antagonistsmentioning
confidence: 98%
“…In another study, cyclo(L-Phe-L-Pro) produced by Vibrio vulnificus was found to activate the quorum sensing on an E. coli biosensor strain by modulating the expression of the gene encoding OmpU protein [231]. Finally, cyclo(L-Phe-L-Pro) and cyclo(L-Pro-L-Tyr) produced by Lactobacillus reuteri, were reported to interfere with quorum sensing in the Gram-positive S. Aureus [41,221,227,[232][233][234].…”
Section: Quorum-sensing Agonists and Antagonistsmentioning
confidence: 98%
“…Very recently, two groups published the structure of the same P 450 from Streptomyces sp. NRRL F-5053, termed NzeB and Nas F5053 , respectively (Shende et al 2020 ; Sun et al 2020 ). It was proposed that the dimerisation of cWP catalysed by this enzyme would also be via a radical-mediated mechanism (Fig.…”
Section: Structural Basis and Reaction Mechanismsmentioning
confidence: 99%
“…8 ) (Shende et al 2020 ). In contrast to CYP121, this dimerase only forms one radical at nitrogen N1 (Sun et al 2020 ) or N12 (Shende et al 2020 ) after abstraction of one hydrogen by compound I (intermediate 1). In the mechanism proposed by Shende et al ( 2020 ), the resulting radical then shifts to C3 after cyclisation between N12 and C2 (intermediate 2).…”
Section: Structural Basis and Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a cytochrome P450 has been identified that can catalyze both the CDP dimerization and cyclization towards bioactive CDP-derived natural products with interesting bioactivities ( Figure 2 ) [ 96 ]. Mutagenesis of other cytochrome P450s gave access to catalysts for CDP synthesis with good regio- and stereo-specificity, and chemical versatility [ 97 ]. Whole-cell biocatalysts were used to attain heterodimeric CDPs, with Mycobacterium smegmatis demonstrating to be a more robust and efficient organism, than the commonly used Escherichia coli or Streptomyces systems [ 98 ].…”
Section: Synthesis Of Cdpsmentioning
confidence: 99%